Implementing SARS-CoV-2 routine surveillance in antenatal care in Zambia, 2021–2022: best practices and lessons learned - Tannia Tembo; Elizabeth Heilmann; Bupe Mulenga Kabamba; Sombo Fwoloshi; Kalubi Kalenga; Felix Chilambe; Mpanji Siwinga; Marie-Reine Rutagwera; Maximillian Musunse; Chabu Kangale; Samuel Yingst; Ruchi Yadav; et al. (BMC Public Health)
Abstract Background In Zambia, the true extent of SARS-CoV-2 infections is unknown because initial surveillance focused on patients with symptoms or severe disease. Antenatal sentinel surveillance had not been used to assess infection trends. The ANC COVID-19 surveillance study sought to determine SARS-CoV-2 seroprevalence and COVID-19 vaccine uptake among pregnant women. We provide insight into the study implementation, challenges encountered, best practices, and lessons learned. Methods A repeated cross-sectional seroprevalence survey was implemented at 39 health facilities in four districts from September 2021 to September 2022. Pregnant women aged 15–49 years were enrolled at their first antenatal care visits. An electronic questionnaire gathered demographics and other COVID-19 related information from consenting participants. A dried blood sample was collected to detect IgG antibodies using a multiplex bead assay. Seropositive results were categorized as infection, infection and vaccination or infection based on anti-RBD and anti-nucleocapsid test results. Problems and their root causes were identified as they occurred. Practical problem-solving strategies were devised, implemented, and monitored to ensure that goals were accomplished. Results In the primary analysis, 7% of the 9,221 samples collected from participants were not tested because they were missing. COVID-19 vaccine uptake of 9,111 pregnant women was assessed. Approximately 64% of participants were cumulatively seropositive for SARS-CoV-2 antibodies. Seroprevalence increased from 27.8% in September 2021 to 56.6% in July 2022. We observed an increase in vaccine coverage (0.5–27%) over time. Women aged 40–49 years old, without education and with prior COVID-19 infection were associated with higher vaccine uptake. The Delta variant of COVID-19 and the reallocation of health facilities between two partners delayed surveillance activities and increased the cost of implementation (e.g., the purchase of additional calibration and validation kits and DBS cards). Protocol deviations were attributed to the lack of experience in conducting research but, the district RAs repeatedly trained health facility staff to enhance their research knowledge. Conclusions Incorporating SARS-CoV-2 surveillance into routine antenatal care is feasible and potentially sustainable when existing health system infrastructure, human resources, and surveillance systems are leveraged. Yet, careful planning is needed to anticipate implementation challenges and ensure high-quality data collection.